Concentration prediction and spatial origin analysis of criteria air pollutants in Shanghai. (15th June 2023) - Liu, Ying; Yang, Xinxin; Tan, Jianguo; Li, Mingli
Abstract: Severe air pollution events still occur frequently in Shanghai. In order to predict when Shanghai air quality satisfies the National Ambient Air Quality Standards of China (NAAQSC) and identify potential source areas of criteria air pollutants for the regional joint prevention and control of air pollution, concentration data of PM2.5, PM10, SO2, NO2 and O3 were collected in 2014–2022 at fourteen monitoring sites across Shanghai and surrounding areas. A first – order rate equation with harmonic regression analysis was employed for time series analysis and concentration prediction. Decreasing concentrations were observed widely over all sites except O3 and NO2 . It is very likely that the secondary NAAQSC standards for PMx, and SO2 would be met by 2025 and O3 and NO2 would likely become the critical pollutants that determine air quality level after 2025. Regional transport was predominant for PMx and SO2 pollution. A 3D – CWT multisite joint location method was developed to identify their potential source areas at different spatial resolutions. Weighting function correction was assigned via information entropy of endpoint numbers in each cell. A probabilistic parameter WI PSA was proposed to quantify and normalize the probability that grid cells are source areas in order to achieve fourteen – site joint location, and it was comparable and compatible at different spatial resolutions. Potential source areas of PM2.5 and PM10 were similar, including Henan, Shandong, Hebei and Anhui, while origin domains of SO2 mainly covered Henan and Hebei. In all seasons, air pollution that was transported to Shanghai (i.e., PMx and SO2 ) originated mainly from the North China Plain; the contribution of marine sources was neglectable. Graphical abstract: Image 1 Highlights: Declining concentrations of PMx and SO2 were observed widely in Shanghai. Local secondary standards for PMx and SO2 would likely be met by 2025. Regional transport was predominant for PMx and SO2 pollution. 3D-CWT multisite joint location identified accurately their potential source areas. In all seasons Shanghai PM pollution originated mainly from the North China Plain.